Hybrid Optimal Approximation of MIMO System - N. Vijaya Anand, Ragaleela Dalapati Rao, Padmanabha Raju Chinda (International Journal of Control and Automation, 2020)
Another model reduction technique of linear time invariant multi variable system is suggested using the eminence of Cuckoo search calculation. The denominator polynomial of the reduced order transfer matrix is determined by Routh approximation method to maintain the stability of higher order system. whereas the numerator polynomial of the lower order transfer function matrix is checked by limiting Integral Square Error (ISE) between the transient responses of original and reduced order models using Cuckoo search. The effectiveness of the algorithm is proved through a Single Machine Infinite Bus (SMIB) power system.